Subcarpathian Rusyns in the debates of the Chamber of Deputies of the inter-war Czechoslovak Republic - Petr Kokaisl (Kulturní Studia, 2023)
The paper presents a very different view of the Rusyn question in inter-war Czechoslovakia through the eyes of Rusyn representatives from across the spectrum of political parties in the Czechoslovak parliament. Although Subcarpathian Rus and its inhabitants were often idealised in Czechoslovakia for their unspoilt nature and patriarchal character, and Czechoslovak public opinion was very favourable towards the region, some Rusyn politicians certainly did not share this ideal. The Communist deputies in particular criticised all government policies and the persistence of general backwardness, but the question of the region’s autonomy was probably the most prominent among the Czechoslovak deputies representing Subcarpathian Rus. The paper highlights four main issues that emerged most frequently in the parliamentary debates: the quest for autonomy, the solution to the poor economic situation, the situation in education and disputes over the use of the language, and the dual treatment of Rusyns living in Slovakia and in Subcarpathian Rus.